Smart Governance Transformation in Indonesian Local Administration - Yusri Maulana, Rio; Usman, Usman; Arief Rakhman, Moh.; Beriansyah, Alva; Firmansyah, Anry; Decman, Mitja; Jorgi Sutan, Arissy (Iapa Proceedings Conference, 2024)
This research delves into the pivotal role of digital government evolution in enhancing local government performance through smart governance concepts. Focused on Indonesia's transformative journey, the study highlights the government's shift towards the Electronic-based Government System (SPBE) to address inefficiencies, bureaucratic challenges, and corruption. Jambi City, an active participant in the 100 Smart City Movement, serves as a specific case study. Using qualitative methods, the research aims to uncover insights into the challenges and future potential of digital transformation at the local level. Despite hurdles such as regulatory barriers and limited resources, the study identifies opportunities for success, especially through stakeholder collaboration and public-private partnerships. The findings emphasize the importance of a collaborative approach in propelling digital transformation efforts for effective public service delivery. This research has significant implications for policymakers, practitioners, and academics interested in the nexus of technology and government in developing countries.